The neonatal transfer process through the lens of neonatologists at public hospitals in South Africa - Pradeep Ashokcoomar; Raisuyah Bhagwan (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2022)
Background: Neonatal care is provided by various levels of healthcare facilities in South Africa. Intensive care for neonates is only provided at the higher levels, hence the need for transfers from lower-level to higher-level facilities (e.g. primary hospitals to tertiary hospitals) or across levels of facilities, particularly when life-threatening situations arise (e.g. cardiac deterioration, respiratory deterioration and desaturation).